Double mutants of Saccharomyces cerevisiae with alterations in global genome and transcription-coupled repair. - Verhage, R A (1996)
The nucleotide excision repair (NER) pathway is thought to consist of two subpathways: transcription-coupled repair, limited to the transcribed strand of active genes, and global genome repair for nontranscribed DNA strands. Recently we cloned the RAD26 gene, the Saccharomyces cerevisiae homolog of human CSB/ERCC6, a gene involved in transcription-coupled repair and the disorder Cockayne syndrome. This paper describes the analysis of yeast double mutants selectively affected in each NER subpathway. Although rad26 disruption mutants are defective in transcription-coupled repair, they are not UV sensitive. However, double mutants of RAD26 with the global genome repair determinants RAD7 and RAD16 appeared more UV sensitive than the single rad7 or rad16 mutants but not as sensitive as completely NER-deficient mutants. These findings unmask a role of RAD26 and transcription-coupled repair in UV survival, indicate that transcription-coupled repair and global genome repair are partially overlapping, and provide evidence for a residual NER modality in the double mutants. Analysis of dimer removal from the active RPB2 gene in the rad7/16 rad26 double mutants revealed (i) a contribution of the global genome repair factors Rad7p and Rad16p to repair of the transcribed strand, confirming the partial overlap between both NER subpathways, and (ii) residual repair specifically of the transcribed strand. To investigate the transcription dependence of this repair activity, strand-specific repair of the inducible GAL7 gene was investigated. The template strand of this gene was repaired only under induced conditions, pointing to a role for transcription in the residual repair in the double mutants and suggesting that transcription-coupled repair can to some extent operate independently from Rad26p. Our findings also indicate locus heterogeneity for the dependence of transcription-coupled repair on RAD26.